The Impact of Workload and Negative Work Environment on Employee Work Motivation - Sugiarti, Endang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Employee work motivation is a crucial factor in productivity and quality of work in the workplace. However, high workloads and negative work environments can hinder employee work motivation. This research aims to analyze the relationship between workload and negative work environment and employee work motivation. Apart from that, this research also aims to evaluate specific factors in workload and work environment that most influence employee work motivation. The research method used is a quantitative survey using a questionnaire distributed to the employees of PT. Fouher Popular Internasional, numbering 70 people. Descriptive statistical analysis and regression were used to identify relationships between research variables. The research results show that there is a negative relationship between workload and a negative work environment and employee work motivation. Specific factors such as time pressure, lack of support from colleagues, and lack of clarity in tasks have a significant impact on employee work motivation.